THE CONSUMER ATTITUDE TOWARDS SOCIAL MEDIA ADVERTISING AND THE INFLUENCE OF CORPORATE REPUTATION ON CONSUMER RESPONSE - Wassan, Faheemullah; Yousaf, Usman (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2017)
The purpose of this study is to examine the influence of corporate standing and attitude towards social media on consumer response. Social media advertising is progressively adopting plots in specialists and researchers. We had assumed total respondents 200 and we achieved the target. Meanwhile, we adopted the convenience sampling technique in this research. We distributed the questionnaires in order to collect and analyze the data while using linear regression. And that helped us in the compilation of the research work. We found a significant relationship between the consumer’s attitudes toward social media advertising and their responses. Again, it was noted that corporate reputation significantly influences this relationship absolutely between the relationship of corporate standing and consumer response. This study is limited to the convenience audience and it is designed as a cross-sectional only. So, there remains a lot of gaps to be filled up in sense of the Area or we can say it as a geographical perspective and the audience’s perspective that we call the target market of the research. And it makes it difficult to generalize the findings and assume for variations that happened in the attitude of consumers. This study says about the influential role of the corporate reputation in consumer’s attitudes toward social media advertising.